KERJASAMA LAUNDRY SECTION DENGAN DEPARTMENT LAIN PADA HOTEL GRAND JATRA KOTA PEKANBARU - Muhammad Wahyudi Sembiring; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Laundry Department is one of the departments in the hotel that is responsible for washing, both washing guest clothes (laundry, dry cleaning and pressing), employee uniforms and hotel linens (house laundry) and washing clothes or linen from outside the hotel (outside laundry). . Therefore, the laundry must cooperate with other departments at the hotel. This study aims to determine the cooperation of the laundry section with other departments, the constraints and efforts made at the Grand Jatra Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. The data collection techniques used were observation, documentation, and interviews with laundry managers, laundry supervisors and laundry employees at Grand Jatra Hotel Pekanbaru. After conducting interviews with resource persons, the authors conclude that laundry cooperation with other departments is quite good, because the laundry staff have implemented in accordance with the directions set by the laundry manager. Keywords: cooperation, laundry, other departments.